On a Question Raised by Brown, Graham and Landman - Jungić, Veselin (Sarajevo Journal of Mathematics, 2024)
We construct non-periodic 2-colorings that avoid long mochromatic progressions having odd common differences. Also we prove that the set of all arithmetic progressions with common differences in ( N!-1) N!( N!+1) - { 0} does not have the 2-Ramsey property. 2000 Mathematics Subject Classification. Primary 11B25; Secondary 05D10